Creative industries : contracts between art and commerce - Caves, Richard E. 1931- (Cambridge ; London : Harvard University Press, 2000)
"This book explores the organization of creative industries, including the visual and performing arts, movies, theater, sound recordings, and book publishing. In each, artistic inputs are combined with other, "humdrum" inputs. But the deals that bring these inputs together are inherently problematic: artists have strong views; the muse whispers erratically; and consumer approval remains highly uncertain until all costs have been incurred." "To explain the logic of these arrangements, the author draws on the analytical resources of industrial economics and the theory of contracts. He addresses the winner-take-all character of many creative activities that brings wealth and renown to some artists while dooming others to frustration; why the "option" form of contract is so prevalent; and why even savvy producers get sucked into making "ten-ton turkeys," such as Heaven's Gate."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Arts -- Economic aspects -- United States